2013
DOI: 10.1088/1674-1056/22/1/010302
|View full text |Cite
|
Sign up to set email alerts
|

Dirac equation for the Hulthén potential within the Yukawa-type tensor interaction

Abstract: Using the Nikiforov-Uvarov (NU) method, pseudospin and spin symmetric solutions of the Dirac equation for the scalar and vector Hulthén potentials with the Yukawa-type tensor potential are obtained for an arbitrary spin-orbit coupling quantum number κ. We deduce the energy eigenvalue equations and corresponding upper-and lower-spinor wave functions in both the pseudospin and spin symmetry cases. Numerical results of the energy eigenvalue equations and the upper-and lower-spinor wave functions are presented to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
45
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 56 publications
2
45
0
1
Order By: Relevance
“…In spherical coordinates, the Dirac equation for fermionic massive spin− 1 2 particles interacting with arbitrary scalar potential S(r), the time-component V (r) of a four-vector potential can be expressed as ( [14,15,59,60], and Refs. therein)…”
mentioning
confidence: 99%
“…In spherical coordinates, the Dirac equation for fermionic massive spin− 1 2 particles interacting with arbitrary scalar potential S(r), the time-component V (r) of a four-vector potential can be expressed as ( [14,15,59,60], and Refs. therein)…”
mentioning
confidence: 99%
“…On the other hand, the efficacy of the tensor potential on spin (pseudospin) doublets has been recently studied [30][31][32][33][34][35][36].…”
Section: D(s(r)−v(r)) Drmentioning
confidence: 99%
“…Those authors [30][31][32][33][34][35][36] showed that the tensor potential removes degeneracies between the energy states that form a pseudospin or spin doublet.…”
Section: D(s(r)−v(r)) Drmentioning
confidence: 99%
“…The potential has successfully accounted for some of the existing data in nuclear, particle, atomic, condensed matter, and chemical physics and has therefore been the subject of some related works in both nonrelativistic and relativistic regimes [23][24][25][26]. The Hulthén potential is a special case of the ManningRosen potential.…”
mentioning
confidence: 99%